Problematic issues and ways to solve them during reverse engineering of compressor design units - A. F. Sarmanaeva; N. V. Sokolov; O. Yu. Paranina; V. V. Kuzovov; Yu. V. Sidorova; I. S. Davletshin; I. N. Lotfullin; M. V. Korshunov (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
A significant part of the compressor fleet in Russia consists of foreign-made centrifugal and screw compressors, which, with operating time and depreciation, require repair according to regulations or modernization due to changed technological operating conditions. The supply of spare parts needed for repairs has become more complicated due to the rise in cost or lack of logistics. This leads to the problem of maintaining the compressor equipment in working order or its downtime. The manufacture of spare parts is problematic due to the lack of design documentation from operating organizations. The offer of reverse engineering services for spare parts and compressor assemblies by specialists of JSC «NIIturbocompressor n. a. V. B. Shnepp» makes it possible to improve and solve the problem of maintaining the effective condition of foreign equipment. At the same time, the article describes the problems that arise during reverse engineering of rotors of centrifugal and screw compressors, the spatial profile of impellers and fluid film bearings. The main points contributing to the successful completion of reverse engineering tasks are indicated, the accuracy of 3D scanning is determined, and methods for setting nominal dimensions and deviation tolerances are presented.